ANALISIS PERBANDINGAN SISTEM ANTRIAN MODEL M/M/1 DAN M/M/S UNTUK PELAYANAN PBB DI DPKAD KABUPATEN PURWAKARTA - Edi Susanto; Fidianti SE (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2016)
Research on the comparative analysis of single channel queuing system and multiple channel query system with 2 fasilties and 3 facilities. This study aims to investigate how the optimal number of facilities due to the large queues waiting for their turn receive services especially Pajak Bumi dan Bangunan in the Office of Dinas Pengelola Keuangan dan Aset Daerah Kabupaten Purwakarta.The analytical method used is the model M / M / 1 for single channel system query and M / M / S is used for multiple channel query system. based on the results of the analysis using the model found that the results of a query using a single channel system services Pajak Bumi dan Bangunan certainly not optimal due to the ability of the service itself 12 people per hour. On the other side using the model M / M / S found the average amount of time service during rush hour period 10:00 to 11:00 of 0:15 hours or can be 9 minute and an average queue length 1.0667. In contrast to the number 3 facility, the taxpayer at a busy period 10:00 to 11:00 can wait with a difference of only 0.0923 hours or 5:54 minutes and the number of queues waiting with an average of 0.1446.Suggestion research obtained in order to use the three facilities while maintaining the service with optimal. So that all service activities will not be interrupted and did not make the queue longer taxpayer.Keyword : Queue, single channel queuing system and multiple channel query system, services, tax payer